Entrepreneurial ecosystems structure, a measurement framework and first findings in african low income countries - (:unkn) unknown (My University, 2022)
One of the most important factors for stimulating well-being and economic development in a territory is entrepreneurship. The environment in which it emerges is the Entrepreneurial Ecosystem. Therefore, the understanding of its structure and configuration is essential to build stimulation strategies. However, its structural and configurational model is currently misunderstood, mainly because of the theoretical confusion between its economic understanding and an organizational explanation of its structure and processes. The result is a wide dispersion of conceptual frameworks in an abundant literature centered on an economic theoretical theory, limiting the emergence of convincing organizational theories, as noted by many leading researchers. Throughout this doctoral journey, we strive to bring together what is scattered, leading to the proposal of an original measurement method. Based on a quantitative methodological orientation, we are led to discover clues of a structural model, based on the mobilization of network theory applied to entrepreneurial ecosystems. This article-based thesis presents five complementary articles, systematically studying the application of this method in Africa, providing interesting results on the impact of entrepreneurial ecosystems on entrepreneurial dynamics. We find how information diffusion and proximity factors in entrepreneurial ecosystems are correlated with strong entrepreneurial dynamics, and identify a resource distribution factor for entrepreneurs. We find that when these Entrepreneurial Ecosystem attributes are weak, a process of discontinuity occurs in the distribution of resources to entrepreneurs, leading to a decrease in the associated entrepreneurial dynamics. More than a thesis, this work constitutes the first steps of a research program aimed at better understanding how one Entrepreneurial Ecosystem can be more conducive to entrepreneurial dynamics than another.
Keywords: African Research